"The Calendar is Crucial": Coordination and Awareness through the Family Calendar - Neustaedter, Carman; Brush, A.J.; Greenberg, Saul (2006)
Everyday family life involves a myriad of mundane activities that need to be planned and coordinated. We describe findings from studies of 44 different families’ coordination routines to understand how to best design technology to support them. We outline how a typology of calendars containing family activities is used by three different types of families—Monocentric, Pericentric, and Polycentric—which vary in the level of family involvement in the calendaring process. We describe these family types, the content of family calendars, the ways in which they are extended through annotations and augmentations, and the implications from these findings for design.
Carman Neustaedter & Saul Greenberg are affiliated with the Department of Computer Science, University of Calgary, Calgary, Alberta, Canada [carman, saul]@cpsc.ucalgary.ca